2002
DOI: 10.1111/j.1365-2621.2002.tb10295.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Granule Size and Size Distribution on Rheological Behavior of Chemically Modified Potato Starch

Abstract: The effects of granule size and size distribution on rheological behavior of hydroxypropylated and phosphate cross-linked potato starch (HPS) were studied by steady and dynamic viscoelasticity measurements. The rheological behavior of starch dispersions was strongly influenced by granule size and granule-to-granule interaction. Average granule size of HPS dispersion at high concentration was smaller than that at low concentration. Time dependence of viscosity was quite different depending on shear rate; thixot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
6
1
Order By: Relevance
“…All of the modified starches showed wide and low endothermic peaks between 38 and 72 °C. Similar results were reported by Singh et al [ 4 ], Morikawa and Nishinari [ 44 ], Liu et al [ 45 ], and Przetaczek-Rożnowska and Fortuna [ 12 ] for native potato starch. The onset temperature ranged from 38.6 to 46.5 °C and increased over the modification time.…”
Section: Resultssupporting
confidence: 89%
“…All of the modified starches showed wide and low endothermic peaks between 38 and 72 °C. Similar results were reported by Singh et al [ 4 ], Morikawa and Nishinari [ 44 ], Liu et al [ 45 ], and Przetaczek-Rożnowska and Fortuna [ 12 ] for native potato starch. The onset temperature ranged from 38.6 to 46.5 °C and increased over the modification time.…”
Section: Resultssupporting
confidence: 89%
“…6 lipids [4,25]. Rheological behavior of native potato starch pastes was observed to be strongly influenced by the granule size distribution, granule shape and amylose content [7,14,19,20,26,37]. The control corn and potato starches showed rheological properties that differed somewhat from those of their native counterparts.…”
Section: Cultivarmentioning
confidence: 99%
“…Singh et al (16) reported that cross-linking strengthened the bonding between starch chains and increased the resistance of granular swelling, leading to lower viscosity. It suggested that the distinct rheological changes were possibly attributed to a change in the starch granular structure by cross-linking (32). When pectin and xanthan gum were incorporated in the RS4 suspension, both G' and G" increased with increasing levels of the hydrocolloids used.…”
Section: Resultsmentioning
confidence: 97%